2022
DOI: 10.13057/biodiv/d190354
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Attractiveness of subterranean termite Coptotermes formosanus to plant leaf extracts

Abstract: Abstract. Indrayani Y, Muin M, Adilla C, Yoshimura T. 2018. Short Communication: Attractiveness of subterranean termite Coptotermes formosanus to plant leaf extracts. Biodiversitas 19: 1176-1180. Plant-derived compounds have many potential uses. One such use is in agriculture for managing pests with less risk than with synthetic compounds that are toxicologically and environmentally undesirable. The current study focuses on the potential use of leaf extracts from five tropical plant species in attractant bait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…The effect of concen-tration on attractivity is also supported byTascioglu et al (2012), who stated that concentration influences retention. Retention is closely related to the amount of material (chemical compounds) that constitutes the concentration.Research on the activity of plant extracts against termites has been previously conducted Indrayani et al (2018). examined the attractiveness of five plant types(bay leaves, cloves, eucalyptus, basil, and cinnamon).This study found more termites on filter paper treated with clove, eucalyptus, and cinnamon leaf extracts than on filter paper that was not given extracts, and was inversely proportional to filter paper treated with basil and bay leaf extracts.…”
mentioning
confidence: 97%
“…The effect of concen-tration on attractivity is also supported byTascioglu et al (2012), who stated that concentration influences retention. Retention is closely related to the amount of material (chemical compounds) that constitutes the concentration.Research on the activity of plant extracts against termites has been previously conducted Indrayani et al (2018). examined the attractiveness of five plant types(bay leaves, cloves, eucalyptus, basil, and cinnamon).This study found more termites on filter paper treated with clove, eucalyptus, and cinnamon leaf extracts than on filter paper that was not given extracts, and was inversely proportional to filter paper treated with basil and bay leaf extracts.…”
mentioning
confidence: 97%